Діаспорні словники синонімів української мови - Samoilova, Iryna (Wiener Slawistischer Almanach, 2023)
The article considers the features of the description of linguistic units in the Dictionary of Ukrainian Synonyms by A. Bahmet and the features of the editing of dictionary entries in the Concise Dictionary of Ukrainian Synonyms by P. Derkach. Both dictionaries are diaspora editions.